An Anatomy of the Chinese selectocracy. Issue 3 (2nd September 2018) - Yao, Yang
ABSTRACT: The Chinese regime is a self-contained polity that is best described by selectocracy, i.e. a polity that selects officials by a centralized mechanism. The Chinese Communist Party (CCP) is the selectorate. Throughout the process of reform, the party has been de-politicized, so the central government has become disinterested with regard to the conflicts in society, which enables it to adopt identity-blind and growth-enhancing policies. The selectoracy's selection process is open, competitive and meritocratic. It puts more emphasis on responsibility, not accountability, as incentive to illicit performance from local officials. This ensures that the central government's policies are carried out in the country.